A pilot study demonstrating the identification of Trypanosoma brucei gambiense and T. b. rhodesiense in vectors using a multiplexed high-resolution melt qPCR - Garrod, Gala; Adams, Emily R.; Lingley, Jessica K.; Saldanha, Isabel; Torr, Stephen J.; Cunningham, Lucas J. (PLOS Neglected Tropical Diseases, 2020)
Author summary With global cases of Human African Trypanosomiasis (HAT) reaching pre-elimination numbers, identifying areas of trypanosome transmission becomes increasingly important. With decreasing numbers of cases, the cost of identifying each positive case increases. Screening for trypanosomes in tsetse flies instead of in the human host allows for a faster, more cost-effective and efficient method of detecting areas in which parasite transmission is on-going. Molecular tools such as PCR play a critical role in molecular identification of parasites in vectors. However, at present, multiple PCRs are required to confirm the presence or absence of human infective trypanosomes. Here we present a novel assay which allows for the screening of both species of trypanosomes responsible for HAT in one assay. This method eliminates the need for multiple assays per sample, produces results which are easier to interpret, and reduces the risk of contamination of samples. We found the assay to be as sensitive as the current gold-standard PCR when evaluated on a subset of wild tsetse flies. With further field evaluation, this method could provide an alternative monitoring method for HAT, which can be used leading up to elimination and maintained once elimination has been achieved.